THE SCIENTIFIC CONTRIBUTION OF KEYNES IN THE DEVELOPMENT OF THE THEORY OF PUBLIC, FINANCIAL AND MONETARY REGULATION - CHYRAK, Iryna (Scientific journal «World of Finance», 2022)
Introduction. Nowadays in conditions of growing instability of the market economy more and more attention of scientists is paid to the analysis of both existing approaches to the regulation of economic processes and the development of new ones. A particular attention is paid to the theory of John Maynard Keynes, and in the programs of governments all around the world Keynesian recommendations are widely used to stimulate aggregate demand in a crisis in the economy through financial and monetary regulation.The purpose of the article is to summarize the scientific contribution of John Maynard Keynes in the development of the theory of public, financial and monetary regulation and focus on the peculiarities of the impact of individual factors on the value of effective aggregate demand.Results. Both the government and political activity and scientific contribution of John Maynard Keynes to the development of world economic thought were analyzed. The theoretical approaches of the scientist to substantiation of necessity of macroeconomic regulation in the conditions of strengthening of economic and financial instability and overcoming of the crisis phenomena in economy were generalized. It was found that, according to the scientist, the solution of important problems of the market economy is possible on the basis of the formation of effective demand for resources, which can be regulated through financial and monetary policy instruments. It was established that the main provisions of Keynesian theory remain in the arsenal of economics, and its recommendations for stimulating effective aggregate demand are widely used by governments around the whole world.Conclusions. It is shown that the main provisions of the Keynesian theory remain in the arsenal of economic science and largely determine its current orientation, although they have undergone a certain evolution in the development of modern Keynesians, who take into account today’s economic realities.